The Teacher’s Role in Enhancing Early Childhood Independence Through a Deep Learning Approach - Alin Mentari; Asep Kurnia Jayadinata; Gia Nikawanti; Heni Puspita Sari (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Independence in early childhood is not limited to performing daily tasks autonomously, but also encompasses broader dimensions such as initiative, self-confidence, responsibility, discipline, emotional regulation, and social interaction. This study aims to describe the teacher’s role in fostering children’s independence through a mindful and context-based deep learning approach. The research involved one classroom teacher and 12 children aged 5–6 years in Class B at Trisula Perwari Kindergarten, Purwakarta. A qualitative approach with a case study design was employed, using observation, interviews, and documentation for data collection. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that teachers play essential roles as facilitators, motivators, and guides in developing indicators of responsibility, initiative, and adaptability through intentional and contextual learning practices. Furthermore, the partnership between the school and parents is identified as a key factor in ensuring consistent development of children’s independence both at school and at home.